Konsep Sekularisasi Menurut Nurkholis Majid (Studi Atas Pemikiran Sekularisasi Nurcholish Madjid) - Ahmad Miftachul Amin (Manthiq : Jurnal Filsafat Agama dan Pemikiran Islam, 2023)
Abstract: The Concept of Secularization According to Nurkholis Majid (Study of Nurcholish Madjid's Secularization Thought). The background for the emergence of the idea of secularization cannot be separated from the Western world, especially with Christianity. The Western world as a region where the idea of secularization emerged was inseparable from philosophical thought which later influenced the development of science and technology which was later marked by the emergence of the industrial revolution. So that it has a considerable impact on religious conditions or religious affairs, namely the erosion of spiritual values and the human person so that religious affairs are separated from the world. The formulation of the problem in this research is what is the idea of secularization according to Nurkholis Majid? Meanwhile, the aim of this research is to find out the idea of secularization from Nurcholish Madjid's thought. The purpose of this research is to contribute to the study of Islamic thought, especially Islam and modern issues such as secularization. Second, it is hoped that the results of this study will be able to provide new insights in seeing the challenges for Muslims in the future when dealing with issues of modernity such as secularization. This research is a qualitative research. Here the researcher collects data, secondly performs data analysis, the third compiles systematically in the form of a systematic discussion. This type of research is library research (library research) from various literatures whose main object is books, journals, manuscripts, notes and other forms of writing related to Nurkholish Madjid's thoughts. In simple terms, this study carried out several stages, because this study was a systematic study. To facilitate and obtain problem formulations in this study, the authors need to emphasize an approach method, namely the socio-historical approach. Based on the above explanation, it can be concluded that the concept of securelization according to Nurcholish Madjid, is intended to further strengthen the task of humans on earth as khalifah. The function as caliph makes humans have the freedom to regulate and act in order to improve life on earth, as well as provide justification that humans have responsibility for the actions they have done on earth before God.